Easy to strip cable sheath material
By using low-density polyvinyl resin, elastic additives and homemade easy-to-peel additives in optical cable sheath material, the problem of difficulty in peeling and hard texture of existing sheath material is solved, and the easy-to-peelability of sheath material is achieved and anti-aging properties.
Patent Information
- Application Number
- CN202410109903.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2023-03-31
- Filing Date
- 2024-01-26
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-01-26
AI Technical Summary
The existing optical cable sheath material is difficult to peel off during construction, which easily damages the optical fiber, and the hard texture leads to signal attenuation and fiber breakage.
Low-density polyethylene is used as the matrix resin, and elastic additives and easy-to-peel additives are introduced. The easy-to-peel additives are homemade organic-inorganic composites with UV resistance and promotion of peeling, including hyperbranched silicones and nanodioxides. silicon.
The easy peelability and anti-aging properties of the optical cable sheath material are achieved, the risk of fiber damage is reduced, and the thermal elasticity and wear resistance of the sheath material are improved.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sheath materials, and in particular relates to an easily strippable optical cable sheath material. Background Art
[0002] The sheath material is a commonly used protective insulation layer for optical cables. It not only protects the optical cable from damage by the external environment, but also gives or improves the flame retardant properties, elasticity and other properties of the optical cable, thereby improving the service life and application safety of the optical cable. During the construction of optical cable projects, special tools are required to strip and route the optical cables. In this process, special tools can easily damage the optical fiber coating. Therefore, it is necessary to develop an optical cable sheath material that is easy to strip to reduce the damage to the optical fiber during the construction of optical cable projects. Existing sheath materials are often made of high molecular polymers, which have strong adhesion, tear resistance, high hardness, and good protection for optical fibers. This strong adhesion makes it difficult to strip. At the same time, the existing optical cable sheath material is hard and easy to bend, resulting in excessive optical fiber signal attenuation and even optical fiber breakage.
[0003] Based on this, the present invention provides an optical cable sheath material which has good elasticity and is easy to strip. Summary of the invention
[0004] The object of the present invention is to provide an optical cable sheath material that is easy to strip, so as to provide an optical cable sheath material that is easy to strip.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] The easy-to-strip optical cable sheath material comprises the following raw materials in parts by weight: 35-75 parts of low-density polyethylene, 15-30 parts of elasticity additive, 6-15 parts of easy-to-strip additive, and 2-8 parts of compatibilizer.
[0007] Furthermore, the elasticity aid is a thermoplastic polyester elastomer or a thermoplastic polyurethane.
[0008] Furthermore, the compatibilizer is a mixture of polyethylene-maleic anhydride grafted product and EPDM (ethylene propylene diene monomer rubber) grafted maleic anhydride grafted product in any ratio.
[0009] Furthermore, the easy-to-peel auxiliary agent is prepared by the following steps:
[0010] The silica sol, the light-stable aminosilane coupling agent and the anhydrous ethanol are uniformly mixed, heated to 50-65° C., and then the aqueous solution is slowly added dropwise. After the addition is complete, stirring is continued for 6-12 hours, and the mixture is rotary evaporated and dried to obtain an easy-to-peel auxiliary agent, wherein the aqueous solution is composed of anhydrous ethanol, hydrogen chloride and deionized water mixed in a mass ratio of 45-48:1:2, the mass ratio of silicon dioxide, the light-stable aminosilane coupling agent, anhydrous ethanol and the aqueous solution in the silica sol is 3-5:0.3-0.5:25:50-55, the diameter of silicon dioxide is 300-800 nanometers, and the mass fraction of the silica sol is 20-30%.
[0011] In the above reaction, the hydrolysis reaction of the light-stable aminosilane coupling agent is utilized to form a hyperbranched siloxane with a silicon-oxygen bond, and the hydrolysis is carried out in the silica sol. The silanol bond on the surface of silica in the silica sol is utilized to connect the silica particles to the above hyperbranched siloxane system, so that the network structure of the obtained hyperbranched siloxane contains silica, which enhances the mechanical properties and wear resistance of the hyperbranched polysiloxane. At the same time, the low surface energy and low viscosity characteristics of the hyperbranched siloxane give the silica particles excellent fluidity and processability. Even if the obtained stripping agent tends to the surface layer of the sheath material during the processing of the sheath material, the anti-sticking effect of silica is utilized at this time, and the low surface energy characteristics of siloxane make the interface between the sheath material and the optical fiber have a smaller molecular force, thereby providing the stripping performance of the sheath material. In addition, the light-stable aminosilane coupling agent introduces the structure of benzophenone into the stripping agent, so that the stripping agent not only improves the strippability of the sheath material, but also gives the sheath material excellent anti-aging performance.
[0012] Furthermore, the light-stable aminosilane coupling agent is prepared by the following steps:
[0013] The first step is to mix chloroacetyl chloride and dichloromethane evenly, and then slowly drop a mixed solution of 2,4-dihydroxybenzophenone, triethylamine and dichloromethane at -3-0°C with stirring. After the dropwise addition is complete, the mixture is heated to room temperature and stirred for reaction for 4-8h, the reaction is stopped, washed with water, separated, the organic phase is rotary evaporated, cooled and crystallized, filtered, recrystallized with a dichloromethane-petroleum ether system, and dried to obtain a derivative containing dibenzophenone, wherein the molar ratio of chloroacetyl chloride, 2,4-dihydroxybenzophenone and triethylamine is 1.2-3:1:1.2-3, and preferably the molar ratio of chloroacetyl chloride, 2,4-dihydroxybenzophenone and triethylamine is 1.2-1.5:1:1.2-1.5;
[0014] The second step is to uniformly mix the derivative containing diphenyl ketone, triethylamine and dichloromethane, and then slowly drop a mixed solution of aminosilane coupling agent and dichloromethane at -3-0°C with stirring. After the dropwise addition is complete, the mixture is heated to room temperature and stirred for reaction for 2-4 hours. The reaction is stopped, washed with water, separated, the organic phase is rotary evaporated, cooled and crystallized, and dried to obtain a light-stable silane coupling agent, wherein the molar ratio of the derivative containing diphenyl ketone, triethylamine and aminosilane coupling agent is 1-2:1-2:1-2, and preferably the molar ratio of the derivative containing low diphenyl ketone, triethylamine and aminosilane coupling agent is 1:1:1.
[0015] Beneficial effects of the present invention:
[0016] In order to solve the problems mentioned in the background technology, the present invention adopts low-density polyethylene as a matrix resin, utilizes the good processability and improveable properties of low-density polyethylene, introduces an elasticity aid and an easy-to-peel aid, wherein the elasticity aid is a thermoplastic polyester elastomer or a thermoplastic polyurethane, utilizes the excellent thermoelastic properties of the combination of hard segments and soft segments, improves the poor thermoelastic properties of low-density polyethylene, and gives the composite sheath material better thermoelastic properties. At the same time, in order to improve the compatibility of low-density polyethylene and the elasticity aid and the formation of an interpenetrating network, a compatibilizer is introduced to improve the performance of the elasticity aid; and the easy-to-peel aid is a self-made organic-inorganic composite with anti-ultraviolet properties and peeling-promoting properties of the present invention, wherein the organic is a hyperbranched siloxane molecule, and the inorganic is nano-silicon dioxide, which has good fluidity in the low-density polyethylene matrix resin, and gives the composite sheath material excellent easy-to-peel and anti-aging properties. DETAILED DESCRIPTION
[0017] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0018] Example 1
[0019] Preparation of light-stable aminosilane coupling agent:
[0020] The first step is to evenly mix 0.15 mol chloroacetyl chloride and 150 mL dichloromethane, and then slowly drop a mixed solution of 0.1 mol 2,4-dihydroxybenzophenone, 0.15 mol triethylamine, and 100 mL dichloromethane at -3-0°C with stirring. After the dropwise addition is complete, the mixture is heated to room temperature and stirred for 4 hours, the reaction is stopped, washed with water, separated, the organic phase is rotary evaporated, cooled and crystallized, filtered, recrystallized with a dichloromethane-petroleum ether system, and dried to obtain a derivative containing dibenzophenone;
[0021] Step 2: Evenly mix the benzophenone derivative prepared in step 1, 0.1 mol triethylamine, and 160 mL dichloromethane, and slowly drop a mixed solution of aminosilane coupling agent (KH-540) and dichloromethane at -3-0°C with stirring. After the addition is complete, warm to room temperature, stir and react for 2 hours, stop the reaction, wash with water, separate the liquids, rotary evaporate the organic phase, cool and crystallize, and dry to obtain a light-stable silane coupling agent.
[0022] Example 2
[0023] Preparation of light-stable aminosilane coupling agent:
[0024] The first step is to evenly mix 0.12 mol chloroacetyl chloride and 150 mL dichloromethane, and then slowly drop a mixed solution of 0.1 mol 2,4-dihydroxybenzophenone, 0.12 mol triethylamine, and 100 mL dichloromethane at -3-0°C with stirring. After the dropwise addition is complete, the mixture is heated to room temperature and stirred for 6 hours, the reaction is stopped, washed with water, separated, the organic phase is rotary evaporated, cooled and crystallized, filtered, recrystallized with a dichloromethane-petroleum ether system, and dried to obtain a derivative containing dibenzophenone;
[0025] Step 2: Evenly mix the benzophenone-containing derivative prepared in step 1, 0.1 mol triethylamine, and 160 mL dichloromethane, and slowly drop a mixed solution of aminosilane coupling agent (KH-540) and dichloromethane at -3-0°C with stirring. After the addition is complete, warm to room temperature, stir and react for 4 hours, stop the reaction, wash with water, separate the liquids, rotary evaporate the organic phase, cool and crystallize, and dry to obtain a light-stable silane coupling agent.
[0026] Example 3
[0027] Preparation of easy-to-peel additives:
[0028] 15 g of silica sol, 0.4 g of the light-stable aminosilane coupling agent prepared in Example 1 and 25 g of anhydrous ethanol were mixed evenly, heated to 50° C., and then 50 g of the aqueous solution was slowly added dropwise. After the addition was complete, stirring was continued for 12 h, rotary evaporation was performed, and drying was performed to obtain an easy-to-peel auxiliary agent, wherein the aqueous solution was composed of a mixture of 47 g of anhydrous ethanol, 1 g of hydrogen chloride and 2 g of deionized water, the diameter of the silicon dioxide was 800 nanometers, and the mass fraction of the silica sol was 20%.
[0029] Example 4
[0030] Preparation of easy-to-peel additives:
[0031] 25 g of silica sol, 0.5 g of the light-stable aminosilane coupling agent prepared in Example 2 and 25 g of anhydrous ethanol were mixed evenly, heated to 65° C., and then 55 g of the aqueous solution was slowly added dropwise. After the addition was complete, stirring was continued for 6-12 hours, rotary evaporated, and dried to obtain an easy-to-strip agent, wherein the aqueous solution was composed of a mixture of 458 g of anhydrous ethanol, 1 g of hydrogen chloride and 2 g of deionized water, the diameter of the silicon dioxide was 300 nanometers, and the mass fraction of the silica sol was 20%.
[0032] Example 5
[0033] The easy-to-strip optical cable sheath material comprises the following raw materials in parts by weight: 45 parts of low-density polyethylene, 30 parts of elasticity aid, 10 parts of the easy-to-strip aid prepared in Example 3, and 8 parts of a compatibilizer, wherein the elasticity aid is DuPont TPEE 3548 from the United States; the compatibilizer is a mixture of polyethylene-maleic anhydride grafts and EPDM (ethylene propylene diene monomer) grafted maleic anhydride grafts in any ratio.
[0034] Example 6
[0035] The easy-to-strip optical cable sheath material comprises the following raw materials in parts by weight: 75 parts of low-density polyethylene, 15 parts of elasticity aid, 6 parts of the easy-to-strip aid prepared in Example 4, and 2 parts of compatibilizer, wherein the elasticity aid is DuPont TPEE 3548 from the United States; and the compatibilizer is polyethylene-maleic anhydride graft.
[0036] Example 7
[0037] The easy-to-strip optical cable sheath material comprises the following raw materials in parts by weight: 60 parts of low-density polyethylene, 20 parts of elasticity aid, 15 parts of the easy-to-strip aid prepared in Example 3, and 6 parts of compatibilizer, wherein the elasticity aid is DuPont TPEE 3548 from the United States; and the compatibilizer is EPDM grafted maleic anhydride grafted material.
[0038] Comparative Example 1
[0039] Compared with Example 5, the easy-peeling aid prepared in Example 3 was replaced with an equal amount of a substance prepared in the following steps, and the rest remained unchanged:
[0040] 15g of silica sol, 0.4g of KH-540 and 25g of anhydrous ethanol were mixed evenly, heated to 50°C, and then 50g of aqueous solution was slowly added. After the addition was complete, stirring was continued for 12h, rotary evaporation was performed, and drying was performed to obtain an easy-to-peel agent, wherein the aqueous solution was composed of a mixture of 47g of anhydrous ethanol, 1g of hydrogen chloride and 2g of deionized water, the diameter of silicon dioxide was 800 nanometers, and the mass fraction of silica sol was 20%.
[0041] Comparative Example 2
[0042] Compared with Example 5, the easy-to-peel agent prepared in Example 3 is replaced with silicon dioxide in equal parts, and the rest remain unchanged, wherein the diameter of the silicon dioxide is 800 nanometers.
[0043] Comparative Example 3
[0044] Compared with Example 5, the easy-peeling agent prepared in Example 3 was replaced with low-density polyethylene in equal parts, and the rest remained unchanged.
[0045] Example 8
[0046] The sheath materials obtained in Examples 5-7 and Comparative Examples 1-3 were extruded and granulated by a twin-screw extruder to obtain granules, and the following performance tests were performed:
[0047] Elastic properties: The pellets were made into standard samples according to GB / T10402 and tested. The results are shown in Table 1.
[0048] Stripping force of optical cable: the pellets are extruded on the surface of the optical fiber unit and cooled to obtain the finished optical cable, and then tested on a tensile test device using a 90° fixture at a tensile rate of 25 mm / min. The obtained stripping force is shown in Table 1;
[0049] Xenon lamp artificial accelerated aging test: The pellets were made into standard samples according to GB / T 16442.2 and tested at a test temperature of 65°C ± 3°C, relative humidity of (65°C ± 3)%, and a test time of 2000h. The obtained anti-ultraviolet aging properties are shown in Table 1.
[0050] Table 1
[0051]
[0052]
[0053] It can be seen from the data in Table 1 that the anti-aging performance of the optical cable sheath material obtained in Examples 5-7 is better than the corresponding performance of the optical cable sheath material obtained in Comparative Examples 1-3, the elastic performance of the optical cable sheath material obtained in Examples 5-7 is better than the corresponding performance of the optical cable sheath material obtained in Comparative Examples 2-3, and the easy-to-strip performance of the optical cable sheath material obtained in Examples 5-7 is better than the corresponding performance of the optical cable sheath material in Comparative Examples 2-3.
[0054] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0055] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. Easy-to-strip optical cable sheath material, characterized by: The invention comprises the following raw materials in parts by weight: 35-75 parts of low-density polyethylene, 15-30 parts of elasticity additive, 6-15 parts of easy-peeling additive, and 2-8 parts of compatibilizer; The easy-to-peel auxiliary agent comprises the following steps: Mix the silica sol, light-stable aminosilane coupling agent and anhydrous ethanol evenly, heat to 50-65°C, then slowly drop the aqueous solution, continue stirring for 6-12 hours after the dropwise addition is complete, rotary evaporate, and dry to obtain an easy-to-strip auxiliary agent; The light-stable aminosilane coupling agent comprises the following steps: The first step is to mix chloroacetyl chloride and dichloromethane evenly, and then slowly drop a mixed solution of 2,4-dihydroxybenzophenone, triethylamine and dichloromethane at -3-0°C with stirring. After the dropwise addition is complete, the mixture is heated to room temperature and stirred for 4-8 hours. The reaction is stopped and a derivative containing dibenzophenone is obtained after post-treatment. The second step is to mix the derivative containing diphenyl ketone, triethylamine and dichloromethane evenly, and then slowly add the mixed solution of aminosilane coupling agent and dichloromethane at -3-0°C with stirring. After the addition is complete, warm to room temperature, stir and react for 2-4 hours, stop the reaction, and obtain a light-stable silane coupling agent through post-treatment.
2. The easily strippable optical cable sheath material according to claim 1, characterized in that: The elasticity auxiliary agent is a thermoplastic polyester elastomer or a thermoplastic polyurethane.
3. The easily strippable optical cable sheath material according to claim 1, characterized in that: The compatibilizer is a mixture of polyethylene-maleic anhydride grafted material and EPDM-grafted maleic anhydride grafted material in any ratio.
4. The easily strippable optical cable sheath material according to claim 1, characterized in that: The aqueous solution is composed of anhydrous ethanol, hydrogen chloride and deionized water mixed in a mass ratio of 45-48:1:
2.
5. The easily strippable optical cable sheath material according to claim 4, characterized in that: The mass ratio of silicon dioxide, light-stable aminosilane coupling agent, anhydrous ethanol and aqueous solution in the silica sol is 3-5:0.3-0.5:25:50-55, and the mass fraction of the silica sol is 20-30%.
6. The easily strippable optical cable sheath material according to claim 5, characterized in that: The diameter of silica is 300-800 nanometers.
7. The easily strippable optical cable sheath material according to claim 1, characterized in that: The molar ratio of the chloroacetyl chloride, 2,4-dihydroxybenzophenone and triethylamine is 1.2-3:1:1.2-3.
8. The easily strippable optical cable sheath material according to claim 7, characterized in that: The molar ratio of the benzophenone-containing derivative, triethylamine and aminosilane coupling agent is 1-2:1-2:1-2.
Citation Information
Patent Citations
Light stabilizer with ultraviolet ray shielding and absorbing functions and preparation method thereof
CN104788725A
Benzophenone macromolecular photoinitiator and preparation method thereof
CN104987435A